Computational Insight on Bioactive Compound Potential Activity of Kenitu (Chrysophyllum cainito L.) Leaves as PPAR-y Antagonist for Obesity - Rosyada, Nabila Nur; Andyni, Regina Shania; Alvionita, Cicin Vinolia; Narwasthu, Sekararum; Adawiyah, Robiatul; Hermanto, Feri Eko; Kurniawan, Nia; Fatchiyah, Fatchiyah (Universitas Brawijaya, 2024)
Studies reported that kenitu (Chrysophyllum cainito) has the potential as an anti-obesity agent. However, the mechanism underlying that activity remains unknown. On the other hand, targeting PPAR-y has played a beneficial role in regulating obesity. Therefore, this study will explain the anti-obesity potential of natural compounds from C. cainito in modulating obesity through inhibition of PPAR-y. Molecular docking was employed to identify the possibility of several compounds binding with the PPAR-y. Moreover, the stability of the interaction between PPAR-y and each compound was also evaluated using molecular dynamics analysis. The result showed that beta-sitosterol, lupeol, myricitrin, quercitrin, rutin, vitamin A, epicatechin, and chlorogenic acid are worthy of potential as PPAR-y antagonists. In advance, molecular dynamics simulations revealed that chlorogenic acid, quercitrin, and epicatechin were the most stable compounds to interact as an inhibitor of PPAR-y. In conclusion, compounds from star apple have some potential to improve the health status of patients’ obesity through PPAR-y antagonist activity.